Production and perception of English consonants by Yemeni EFL learners - Mohd Hilmi Hamzah; Najah Ahmed Khamis Bin Hadjah (Universitas Pendidikan Indonesia, 2023)
Previous studies on the perception-production correlation focused mainly on transcriptions and native English speaker evaluations for production accuracy assessments; only a few included acoustic measurements. This study aims to investigate the production and perception of six English consonants by Yemeni EFL learners of English using an acoustic measurement of second-language production. It has three objectives: (1) To investigate the extent to which word position influences the accuracy of Yemeni EFL learners’ production of the target consonants, (2) to assess the extent to which word position affects their perception, and (3) to investigate the relationship between the overall production and perception of the investigated sounds. A quantitative research method was employed for collecting data from six Yemeni EFL postgraduate students from Universiti Utara Malaysia (UUM). In the production tasks, the researchers asked the speakers to produce seventy-two words with the target consonants three times in isolation (Experiment 1) and the other three times in a carrier sentence (Experiment 2). The researchers recorded the speakers’ productions with an iPhone and later evaluated them acoustically via Praat. In the perception test, an AXB experiment was conducted. The findings showed that word position significantly affected the production, yet not the perception of the target sounds. Moreover, an insignificant positive moderate correlation was revealed between the overall production and perception of the target consonants. The findings have implications for second-language speech as well as pronunciation instruction. Teachers may put more focus on specific sound environments that lead learners to struggle while producing/perceiving particular English sounds.